Regional Economic Outlook. - Hemisphere Dept., International Monetary Fund. Western (Regional Economic Outlook., 2008)
The main focus of this report is the outlook for the region in the face of the downturn now projected for the U.S. economy and the continuing risks that affect the global outlook. Overall the region is better placed than in the past to navigate the current financial turbulence, given reduced vulnerabilities and stronger policy frameworks. Nonetheless, the report points to risks that the global financial stress could curtail capital flows to the region and world commodity prices could fall more than expected. There are also risks arising from rising inflation and rapid private credit growth in.